(untitled) (Bulletin of criminological association of Ukraine, 2023)
It was found that the self-governance of lawyers is a system of special bodies through which lawyers can independently ensure internal self-organization and self-governance in order to ensure their compliance with the norms of professional ethics and discipline. It was established that the legal status of the self-governing bodies of lawyers is a system of legally defined elements, which in their totality not only determine the place of the specified subjects in certain legal relations, but also outline the boundaries and directions of their activity. It is summarized that the peculiarities of the legal status of the bodies of bar self-government are determined by: the presence of a wide range of subjects of bar self-government; The Law of Ukraine "On Advocacy and Advocacy" provides for a large number of forms of self-government by lawyers; the purpose of the self-government of lawyers is not only to ensure the implementation of guarantees of autonomy and independence in the activities of lawyers, but also to ensure their compliance with the requirements of lawyer ethics and work discipline; self-government activities are regulated by a separate chapter of a special legislative act; the presence of a number of guarantees of self-government activity, in particular: legal, organizational, material and financial.